Feminism, Media Technologies, and Studio XX: An Interview with Kim Sawchuk - Sawchuk, Kim; Tripp, Stephanie (Media-N: Journal of the New Media Caucus., 2013)
Kim Sawchuk is a feminist media studies scholar and a founding member of Studio XX, a feminist-run new media arts collective based in Montreal. A professor in the Department of Communication Studies at Concordia University, she is the former editor of the Canadian Journal of Communication and co-editor of wi: journal of mobile media. Sawchuk’s work encompasses the roles of women in science and technology, as well as issues surrounding media technology access and use by women, elders, and immigrant communities. Her more recent research involves the use of mobile devices by older adults. During a Skype interview with guest editor Stephanie Tripp on March 22, 2013, Sawchuk discussed her collaboration in Studio XX, her research on women and technology, her work on mobile communications technologies, and her outlook on issues facing women working in new media today.

Resoundingly Entangled: Ageing and Memory in Étoile des aînés in Quebec - Grenier, Line; Sawchuk, Kim; Valois-Nadeau, Fannie (A Senior Moment: Cultural Mediations of Memory and Ageing, 2020)